Childhood Separation From Parents and Self-Harm in Adolescence: A Cross-Sectional Study in Mainland China - Zhou, Tao-Jie; Yuan, Meng-Yuan; Ren, Hao-Yang; Xie, Guo-Die; Wang, Geng-Fu; Su, Pu-Yu (Frontiers in Psychology, 2022)
Background: As the prevalence of self-harm among adolescents in Chinese escalates, finding out the potential risk factors associated with self-harm behaviours has aroused much attention. Previous research suggests a robust connection between childhood adversities and self-harm. Objectives: This study aims to explore the association between parent-child separation (occurrence of parental separation, separation status, age at first separation and duration of separation) and series of self-harm (SH) subtypes among Chinese adolescents. Methods: We survey a total of 4,928 middle school students aged from 12 to 18 years at school. Parent-child separation is referred to as the fact that parents leaving their children in rural areas in order for better employment. Self-harm series are deemed as five subtypes -- highly lethal self-harm, less lethal self-harm with visible tissue damage, self-harm without visible tissue damage, self-harmful behaviours with latent damage and psychological self-harm. Multivariate logistic regression is used to explore the associations between parent-child separation and different subtypes of self-harm among adolescents. Results: Paternal separation is associated with each type of self-harm whilst maternal separation is not correlated with highly lethal self-harm. Except for highly lethal self-harm, the other four subtypes of self-harm demonstrate a relation with both length of paternal separation and maternal separation with aOR ranging from 1.23 to 1.63. Individuals who suffer parental separation prior to the age of three are correlated with four types of less-lethal self-harm. Conclusions: The association of parent-child separation with self-harm deserves our attention, and future research is needed to identify the underlying mechanisms.